Analisis Finansial Usaha Pembesaran Udang Vaname (Litopenaeus vannamei) pada Tambak Intensif di PT. Mitra Raya Cemerlang, Kabupaten Probolinggo - Dhymas Anugrah Syah Putra; Intyas, Candra Adi (Politeknik Negeri Sambas, 2022)
This pacific whiteleg shrimp (Litopenaeus vannamei) enlargement business has the name PT. Mitra Raya Cemerlang was established in 2017 in Koloran Hamlet, Klaseman Village, Gending District, Probolinggo Regency, East Java. This study aims to describe the marketing mix and analyze the business’s financial feasibility. Types of quantitative and qualitative research used a purposive sampling technique. The data analysis method used is marketing mix analysis and business feasibility by calculating short-term and long-term investment criteria. The results of the study indicate that in terms of the marketing mix, it is relatively simple to carry out directly at the place of business. Then in terms of business feasibility, in the short term, it is profitably seen from the R/C Ratio value of 3,785, BEP unit 31,533 kg, and BEP sales Rp. 2,459,591,932.98, and RTC 62.44% while in the long term it is feasible to see from the NPV value of Rp. 36,230,109,107, Net B/C Ratio 4.02, IRR 109%, and PP 1 where the sensitivity level is said to be not too sensitive.